1629. Targeted Antimicrobial Use Admission Provides an Actionable Denominator for Antimicrobial Stewardship Programs Evaluating Inpatient Length of Therapy. (26th November 2018) - Dyer, April; Ashley, Elizabeth Dodds; Davis, Angelina; Johnson, Melissa; Jones, Travis; Moehring, Rebekah W
Abstract: Background: Actionable, easy to interpret antibiotic use (AU) metrics provide antimicrobial stewardship programs (ASPs) with clear targets. Current aggregate AU metrics lack the ability to discriminate between long courses in a limited number of patients versus short courses in a large number of patients. Methods: We developed a novel AU denominator termed "targeted antimicrobial use admission, " defined as an inpatient admission in which a selected agent or group of agents was administered. When used with length of therapy (LOT), it provides the average number of days patients receive the targeted agent(s) during inpatient hospital admissions. To demonstrate the added utility of this metric, we used descriptive statistics to compare it to LOT, LOT/1, 000 patient days, LOT/1, 000 admissions, and LOT/admission to quantify intravenous (IV) vancomycin use among 25 hospitals in the Duke Antimicrobial Stewardship Outreach Network (DASON) for calendar year 2017. The metric was also used to compare hospitals to one another and track durations at an example hospital over time. Results: Total LOT included 128, 680 days of IV vancomycin (table). LOT/targeted antimicrobial use admission is the only metric that allows programs to quickly assess agent durations. Conclusion: Stewardship programs seeking to shorten durations of therapy can track this metric over time to determine the impact of their ASP efforts (Figure 1). The metric can also be used to compare average durations of IV vancomycin by hospital to determine when and if agent-focused audit and feedback or antibiotic timeouts may be useful (Figure 2). The network mean provides a target for agent-specific de-escalations, in days, for facilities with longer durations. LOT/targeted antimicrobial use admission provides an actionable metric for quantifying antimicrobial durations. This metric is easy to interpret and can feasibly be captured through the electronic prescribing record to aid in selecting ASP strategy. Disclosures: All authors: No reported disclosures.